Functional Brain Connectivity and Neurocognitive Functioning in Patients With Long-Standing Type 1 Diabetes With and Without Microvascular Complications: A Magnetoencephalography Study - VAN DUINKERKEN, Eelco; KLEIN, Martin; SCHOONENBOOM, Niki S. M; HOOGMA, Roel P. L. M; MOLL, Annette C; SNOEK, Frank J; STAM, Cornelis J; DIAMANT, Michaela (Diabetes (New York, N.Y.), 2009)
Hyperglycemia-associated microvascular disease may underlie changes in cerebral functioning and cognitive performance in patients with type 1 diabetes. Functional connectivity, an indicator of functional interactions and information exchange between brain regions, provides a measure of cerebral functioning. This study addresses functional connectivity and cognition in type 1 diabetic patients with and without proliferative retinopathy, relative to healthy control subjects, using magnetoencephalography. Fluctuations in magnetic field at scalp for Delta, theta, lower and upper alpha, beta, and lower and upper gamma frequency bands were measured using magnetoencephalography. Synchronization likelihood, a measure of functional connectivity, was computed. Using neuropsychological tests, cognitive functioning was assessed and its associations with functional connectivity were determined. Compared with control subjects, type 1 diabetic patients performed poorer on general cognitive ability, information processing speed, and motor speed, irrespective of their microvascular complication status. Functional connectivity, however, was lowest for type 1 diabetic patients with retinopathy, compared with type 1 diabetic patients without microvascular complications and control subjects, whereas type 1 diabetic patients without microvascular complications showed an increase relative to control subjects. Positive associations were found between functional connectivity and executive functioning, memory, information processing speed, motor speed, and attention. Compared with healthy control subjects, functional connectivity and cognition differed in type 1 diabetic patients irrespective of microvascular complication status, indicating that chronic hyperglycemia, among other factors, may negatively affect brain functioning even before microvascular damage becomes manifest. The association found between synchronization likelihood and cognition suggests functional connectivity plays a significant role in cognitive functioning.